Urgensi Pluralisme Menurut Enam Agama Resmi di Indonesia - Shofwan, Arif Muzayin; Maknun, Moch Lukluil (FIKRAH, 2023)
Religion is present on earth to function as a medium to build harmony in life. On the other hand, life in this world is filled with people of different tribes, cultures, ethnicities, religions themselves, and the like. Thus, humanity needs an understanding and application of pluralism for such harmonization. This literature study article aims to reveal the urgency of pluralism according to six official religions in Indonesia. Data analysis uses content analysis by sorting data, classifying it, and analyzing it. The important findings of this study are as follows: First, the manifestation of pluralism is substantially in the form of an attitude of interconnection, which recognizes, appreciates, respects, maintains, and even develops or enriches plural conditions. Pluralism is very important to be used as a medium for building a harmonious life full of peace, harmony, and prosperity in a life of diverse cultures, tribes, nations, religions, ethnicities, and the like. Second, pluralism, in the view of the six official religions in Indonesia, can be used as a medium to build a harmonious life full of harmony and peace. However, local religions other than the six official religions are also very important to be used as a medium to build the intended harmonization. This is because all religions, both official religions and local religions, still have the principle to respect, honor, and maintain the existing diversity.